The The Effect of Using Student Worksheets (LKPD) on Student Learning Outcomes in Cross-Interest Chemistry Subjects - Salsabila Sifi Erlawina; Maefa Eka Haryani (Universitas Lampung, 2025)
This research aims to find out whether there is a significant influence from the use of Student Worksheets (LKPD) on student learning outcomes in cross-interest chemistry subjects in class X of SMA Negeri 2 Indralaya Utara. In this study, it was divided into two classes into an experimental group (with Lavoisier LKPD with KPS) and control (normal LKPD). The data collection technique used consists of two main methods, namely the learning outcome test and the observation sheet. It was concluded that the use of Student Worksheets (LKPD) based on the Law of Lavoisier oriented Science Process Skills (KPS) had a significant effect on student learning outcomes in cross-interest Chemistry subjects in class X of SMA Negeri 2 Indralaya Utara. This was proven through the results of the Independent Samples T-Test which showed a significance value of 0.002 (< 0.05). These findings indicate that KPS-oriented LKPD is effective in increasing student active involvement, conceptual understanding, and achieving more optimal learning outcomes in accordance with the learning objectives of the Independent Curriculum.